HR Trends at the beginning of the 21st century - Emese Braun; Klara Veresne Valentinyi (Trendy v podnikání, 2019)
This article examines and forecasts the HR trends at the beginning of the 21st century through giving a brief summary and comparison of the main forecasts and tendencies. There are quite a few forecasts published by HR experts, but no comparison has been made so far which would help to get a more reliable picture of current and future HR trends. The study gives an account of the main predictions and changes shown by international and national HR specialists to occur at the beginning of the millennium. The research was basically a desktop research relying on secondary data and using document analysis. Similarities of the expected trends were identified, and the secondary data were compared and analyzed, the results were summarized in a table and in a bar chart. The findings clearly show that there are basically four areas that are forecast to be in the focus of change at the beginning of the millennium: digitization, employee satisfaction and talent management, work and assessment processes, and leadership and management. It has been found that in the forthcoming years, HR will experience significant transformation, of which digitization will be the most important area.